A natural spring located at the northeast corner of Banganga Tank - Banganga by Ghosh, Ayan (2023)
Banganga tank is fed by a natural spring located at the northeast corner. It is beleived, this is the point where Lord Rama shot an arrow (bana) into the ground, thereby releasing the waters of the underground Ganges (Patalganga), hence the name Banganga. The water that emerges from the spring is considered pure and used in Hindu rituals.